Politics and Performance in Western Greece Essays on the Hellenic Heritage of Sicily and Southern Italy - Reid, Heather L. (Heritage of Western Greece, 2017)
Because the histories of theater, politics, art, poetry, athletics, and philosophy tend to be studied separately, it is easy to forget how interconnected they were in Western Greece-the coastal areas of Southern Italy and Sicily settled by Hellenes in the 8th and 7th centuries BCE. Hieron I of Syracuse may be remembered as a tyrant, but his political power was inseparable from the theater. Hieron was the patron of the dramatist Epicharmus, who was as much a philosopher as Xenophanes, who was a poet in his own right like Pindar, who was also supported by the tyrant and whose work---like all the others'-was performed for political ends. Even Plato's adventures in Syracuse can be seen as a performance of his own political poetry. This collection of essays from a variety of disciplinary perspectives including archaeology, classics, philosophy, and art history, offers a refreshing new outlook on the ancient cultural interactions of politics and performance in Western Greece.